EFFECTS OF PRENATAL YOGA ON MATERNAL ANXIETY - Vistra Veftisia; Luvi Dian Afriyani (Siklus : Journal Research Midwifery Politeknik Tegal, 2021)
Anxious or depression during pregnancy could harm both the mother and the fetus. Antidepressants did not become beneficial for pregnancy. There were several unconventional treatments for anxiety and depression in pregnancy, one of them was prenatal yoga. Prenatal yoga helps improve mood, but pregnant women do not widely use this technique. This study aimed to determine prenatal yoga's effect on pregnant women's anxiety and depression at Midwife Private Practice "Ibu Alam Sidomukti", Salatiga City. This study was quasi-experimental.  This study sample consists of 20 pregnant women in the case group and 20 peoples in the control group.  Prenatal yoga was held once a week for four weeks in the case group.  The purposive sampling was used to obtain respondents.  Data collection used a questionnaire before and after prenatal yoga, namely two weeks and four weeks after that.  Data analysis in this study using Mann-Whitney test.  The results showed no effect of prenatal yoga performed for two weeks on anxiety (p: 0,893), but it effectively reduces anxiety after four weeks of performing prenatal yoga (p: 0,003).  Prenatal yoga should be done regularly every week in order to reduce anxiety and depression in pregnant women. Keywords: prenatal yoga, anxiety, pregnant women